Uronema marinum Dujardin 1841 - Lee, Sue Yeon; Yoo, Jung Sun; Kim, Seung Tae (Zenodo, 2017)
12. Uronema marinum Dujardin, 1841 (Fig. 12) Material examined. Marine water taken from Hupohang port, Hupo-ri, Hupo-myeon, Uljin-gun, Gyeonsangbuk-do, Korea (N36°40 ʹ 52 ʺ , E129°27 ʹ 23 ʺ ) on April 5, 2017. Diagnosis. Body size about 32-41 × 11-20 μm in vivo; elongate elliptical shape; cytostome in anterior 1/2 to 2/5 of body; spherical single contractile vacuole terminally located; about 12 somatic kineties; 1 caudal cilium 11-16 μm long; M1 composed of 5-7 kinetosomes; M2 slightly longer than M1; M3 short; scutica consisting of 4 or 5 dikinetids, arranged in Y or V-shapes; 1 globular macronucleus, size about 7 × 6 μm; single spherical micronucleus 1.5 μm in diameter. Distribution. Cosmopolitan (Antarctica, Benin, China, Germany, Russia, U.S.A., Korea (this study)). Remarks. The Korean population of U. marinum Dujardin, 1841 can be separated from the Chinese population by the arrangement of scutica (Y or V-shaped vs. always Y-shaped), and the number of scutica dikinetids (4 or 5 vs. 3) (Wang et al. , 2009). Voucher slides. Two slides, including protargol-impregnated specimens, were deposited at the National Institute of Biological Resources, Korea (NIBRPR0000107916, NIBRPR0000107917). Published as part of Lee, Sue Yeon, Yoo, Jung Sun & Kim, Seung Tae, 2017, Brief descriptions of 12 ciliate species previously unrecorded (Protozoa: Ciliophora) in Korea, pp. 15-25 in Journal of Species Research 6 on pages 23-24, DOI:10.12651/JSR.2017.6, http://zenodo.org/record/13164465